Extreme-scale load-aligning rotor: To hinge or not to hinge?. (1st January 2020) - Noyes, Carlos; Loth, Eric; Martin, Dana; Johnson, Kathryn; Ananda, Gavin; Selig, Michael
Highlights: Increased blade length and coning angle for increased power with constrained loads. AEP increased by 13% with 33% longer blade, no increase in flapwise bending moment. A morphing hinge results in an additional 6% of AEP, only minimal increases load. Abstract: Load alignment, balancing the thrust moment with the centrifugal moment, is a promising innovation for extreme-scale wind turbines. Load alignment allows for longer blades, capturing more power, while maintaining similar blade moments. As blades lengthen, larger coning angles are required to balance increasing thrust moments with centrifugal moments. This yields a key question for such extreme-scale load-aligned rotors: should the blades hinge to actively vary coning or simply be fixed at a single coning angle? To answer this, steady and turbulent FAST simulations were conducted on a variety of downwind rotors with different blade lengths and coning angles. The longest rotor without a hinge increased the energy production by 13.4% compared to shortest rotor without an increase in peak blade moments. However, in turbulent wind there was an approximately 100% increase in fatigue loads. When the coning angle was allowed to change slowly as a function of wind speed (by means of a morphing hinge), the power increased by 19% and the peak moments increased under turbulent wind conditions, but only by 40%. Inclusion of teeter with the hinge decreased both the peak flapwise moments and the fatigue damage equivalent loads back to near baseline values while maintaining 12% power production increase. The results show that load alignment can be achieved with a fixed coning angle (pre-alignment) or by a morphing hinge. By enabling a larger swept area at lower wind speeds, a morphing hinge allows for up to a 4.6% power increase compared with a fixed coning angle.